Disease progression in paediatric‐ and adult‐onset sclerosing cholangitis: Results from two independent Dutch registries. (26th June 2019) - Joosse, Maria E.; Haisma, Sjoukje M.; Sterk, Marlou F. M.; van Munster, Kim N.; Ponsioen, Cyriel I. J.; Houwen, Roderick H. J.; Koot, Bart G. P.; de Meij, Tim; van Rheenen, Patrick F.; de Koning, Barbara A. E.
Abstract: Background & Aims: Sclerosing cholangitis (SC) is a severe liver disease leading to destruction of bile ducts. It is believed to run a milder course in children than in adults. To test this assumption, we evaluated time‐to‐complication curves in two independent paediatric‐onset cohorts from the same geographical area. Methods: Short‐term disease outcomes were evaluated with an online clinical registry that was filled with data on children with SC diagnosed between 2000 and 2017 and who were followed bi‐annually thereafter. Long‐term disease outcomes were evaluated in a paediatric‐onset subcohort derived from a previously published population‐based study from the Netherlands. Time‐to‐complication in the first cohort was defined as the time from diagnosis until portal hypertension, biliary obstructions and infections, development of malignancy, or liver transplantation, whichever came first. In the second cohort time‐to‐complication was defined as the time until liver transplantation or PSC‐related death. Results: Median age at diagnosis in the first cohort (n = 86) was 12.3 years. In the first 5 years post‐diagnosis 23% of patients developed complications. The patients in the population‐based study (n = 683) were stratified into those diagnosed before the age of 18 years ('paediatric‐onset' subcohort, n = 43) and those diagnosed after the age of 18 years ('adult‐onset' subcohort, n = 640). Median age at diagnosis was 14.6 and 40.2 years, respectively. Median time‐to‐complication in the paediatric‐onset and adult‐onset subcohorts was not statistically different. Conclusion: Paediatric and adult‐onset SC run a similar long‐term disease course. Paediatricians who treat children with SC should monitor them closely to recognize early complications and control long‐term sequelae.